2007
DOI: 10.1038/sj.jid.5700913
|View full text |Cite
|
Sign up to set email alerts
|

Stratum Corneum Acidification Is Impaired in Moderately Aged Human and Murine Skin

Abstract: Aged skin commonly is afflicted by inflammatory skin diseases or xerosis/eczema that could be triggered or exacerbated by impaired epidermal permeability barrier homeostasis. This defect is linked to reduced epidermal lipid synthesis in humans and in mice of advanced age (i.e., >75 years in human or >18-24 months in mice). We now report that barrier defects in moderately aged humans (50-80 years) or analogously aged mice (12-15 months) are linked instead to defective stratum corneum (SC) acidity. In moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(185 citation statements)
references
References 40 publications
12
168
2
3
Order By: Relevance
“…The results of the present study indicate that skin surface pH increases at all assessed localizations, but significantly at the forehead and cheek. This result is in agreement with other studies [5,36], which found an increase in skin surface pH in age compared with younger men. Man et al [5] assume that the elevated skin surface pH with aging is linked to the simultaneous decrease in the epidermal expression of sodium-hydrogen antiporter (Na + /H + ), as Na + /H + is known as one of the key factors regulating skin surface pH [37].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the present study indicate that skin surface pH increases at all assessed localizations, but significantly at the forehead and cheek. This result is in agreement with other studies [5,36], which found an increase in skin surface pH in age compared with younger men. Man et al [5] assume that the elevated skin surface pH with aging is linked to the simultaneous decrease in the epidermal expression of sodium-hydrogen antiporter (Na + /H + ), as Na + /H + is known as one of the key factors regulating skin surface pH [37].…”
Section: Discussionsupporting
confidence: 83%
“…Man et al [5] assume that the elevated skin surface pH with aging is linked to the simultaneous decrease in the epidermal expression of sodium-hydrogen antiporter (Na + /H + ), as Na + /H + is known as one of the key factors regulating skin surface pH [37]. Further, the increased SC pH negatively influences cutaneous permeability barrier homeostasis and lipid processing, which may have a negative influence on the water-holding capacity of the SC, resulting in lower hydration levels [36,37]. This connection is probable as age-related changes occur simultaneously in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Sweat production is also important for maintaining the acid mantle that regulates the growth of skin commensal organisms (Marples 1965;Weller et al 1996). Consistent with decreased eccrine function, increased age is also associated with defective skin-surface acidity (Choi et al 2007). The specific influence of photoaging on eccrine sweat gland structure and function remains to be elucidated.…”
Section: Effects Of Aging On Skin Barrier and Thermoregulation Functionsmentioning
confidence: 95%
“…In moderately aged (50 to 80 years) individuals, abnormal stratum corneum acidification results in delayed lipid processing, delayed permeability barrier recovery, and abnormal stratum corneum integrity, ion transport and turnover. [40][41][42][43] Flattening of the dermo-epidermal junction at sites that were highly corrugated in youth is the most consistent change found in aged skin 44 and is due primarily to a retraction of the rete ridges. 30 This reduced interdigitation between epidermis and dermis results is less resistance to shearing forces 13,22 as well as a reduced supply of nutrients and oxygen.…”
Section: Epidermismentioning
confidence: 98%